Enrofloxacina e toltrazuril reduzem a infecção por Toxoplasma gondii em células trofoblásticas humanas e em explantes de vilos placentários humanos de terceiro trimestre - Silva, Rafaela José da (2016)
The classical treatment for congenital toxoplasmosis is based on combination of sulfadiazine and pyrimethamine plus folinic acid. Due to teratogenic effects and bone marrow suppression caused by pyrimethamine, the establishment of new therapeutic targets is indispensable to minimize the undesirable effects and improve the control of the infection. Previous studies demonstrated that enrofloxacin and toltrazuril were able to control the infection triggered by Neospora caninum and Toxoplasma gondii. Therefore, the aim of this present study was evaluate the efficacy of enrofloxacin and toltrazuril in the control of T. gondii proliferation in human trophoblast cells (BeWo lineage) and in human villous explants from third trimester. BeWo cells and villous were treated with several concentrations of enrofloxacin, toltrazuril, sulfadiazine, pyrimethamine or association (sulfadiazine + pyrimethamine) in other to verify their viability by MTT or LDH assay, respectively. Next, BeWo cells were infected with T. gondii RH (2F1 clone) or ME49 strain, whereas villous were infected only with RH strain (2F1 clone), after, both cells and villous were treated or not with the same antibiotics and analyzed to T. gondii intracellular proliferation by beta-galactosidase assay (for RH strain) or blue toluidine staining (for ME49 strain). ELISA was performed in the supernatant to evaluate the cytokine profile. Enrofloxacin and toltrazuril did not change strongly the viability in cells and villous. Furthermore, the drugs decreased the parasite intracellular proliferation regardless T. gondii strain in BeWo cells and villous explants when compared to untreated and infected conditions. In BeWo cells infected by RH, enrofloxacin induced high levels of IL-6 low levels of MIF, while both cytokines were upregulated by enrofloxacin and toltrazuril in BeWo cells infected by ME49 strain. Additionally, in villous explantes, enrofloxacin induced high MIF production. Thus, enrofloxacin and toltrazuril were able to control the parasitism in BeWo cells and villous explants, and probably it occurs by modulation of immune response in these cells or tissues and direct action on parasite, but future experiments are necessary to verify this hypothesis.